The Development of Evaluation Tools to Measure Students' Science Literacy on the Solar System Theme - Asy'syakurni, Nurul Afdhilla; Rusilowati, Ani; Sudarmin, Sudarmin (Journal of Innovative Science Education)
Nowadays scientific literacy is a concern in the world of education. Various efforts have been made by the Government to improve students' scientific literacy. Efforts are made by changing the current curriculum. However, this has not been followed by the availability of assessment instruments or evaluation tools used to measure students' scientific literacy. The results of observations carried out show that currently the evaluation tool used is only to measure students’ knowledge. This study aims to develop an evaluation tool based on aspects of scientific literacy competence on the theme of the solar system. This study also aims to determine the scientific literacy profile of students through Item Response Theory (IRT) analysis. The research was conducted with a sample of 256 students of class VIII SMP Negeri 2 Salatiga. IRT analysis using the BILOG MG computer program with a 2-parameter logistic model (2-PL). The results of the item analysis showed that of the 30 items, there was one item (item 25) that had a minus biserial correlation value, so item 25 that no calculations for the next phase. From the analysis of the difficulty level index, 86% of the items have a good difficulty index and all items have a good differentiation of problem index. The results of the students' abilities showed that the average obtained was -0.0143. The mean ability with a minus value indicates that most of the students have low abilities.